2017
DOI: 10.1002/jwmg.21287
|View full text |Cite
|
Sign up to set email alerts
|

Mixed effects of gating subterranean habitat on bats: A review

Abstract: Caves and abandoned mines, roosting environments for many bat species including subterranean obligates, are under human pressure (e.g., recreation) and pose threats to humans. Gating entrances of these subterranean features prevents human entry while protecting habitat for bats. However, bat response to these gates is not well understood and no comprehensive synthesis with species-specific recommendations on protection measures for bat roosts exists. We reviewed literature on effects of gating subterranean hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…Bat activity at multiple scales in a post-wildfire landscape Jemison et al [23] also found that small-bodied bats with low aspect ratio and wing loading were negatively affected by wildfire compared to species with big bodies and long, narrow wings. Bats with lower wing loading and a lower aspect ratio are better suited to maneuvering around and gleaning prey from objects than species with high wing loading and aspect ratio [35,58,59]. However, Buchalski et al [24] found the opposite with Myotis activity higher in areas of high burn severity.…”
Section: Plos Onementioning
confidence: 99%
“…Bat activity at multiple scales in a post-wildfire landscape Jemison et al [23] also found that small-bodied bats with low aspect ratio and wing loading were negatively affected by wildfire compared to species with big bodies and long, narrow wings. Bats with lower wing loading and a lower aspect ratio are better suited to maneuvering around and gleaning prey from objects than species with high wing loading and aspect ratio [35,58,59]. However, Buchalski et al [24] found the opposite with Myotis activity higher in areas of high burn severity.…”
Section: Plos Onementioning
confidence: 99%
“…Bat‐compatible gates, designed with wide horizontal bar spacing for accessibility by bats, prevent human access and protect habitat. Gate designs vary depending on the type of mine feature (e.g., adit [horizontal opening], shaft [vertical opening]) and condition of feature (e.g., sloughing portal [entrance]; Tobin and Chambers ).…”
mentioning
confidence: 99%
“…Older gate designs (i.e., >45 yrs ago) that block 1 or part of an entrance often negatively affected bats and microclimates of caves and mines (Richter et al , Kennedy ); however, responses of species to gates designed specifically for bats (bat‐compatible) varied from negative to positive (Tobin and Chambers ). In general, short‐term studies reported that bats increased energetically demanding behaviors such as circling or fly‐retreating when encountering gates (Spanjer and Fenton , Derusseau and Huntly , Diamond and Diamond ).…”
mentioning
confidence: 99%
See 2 more Smart Citations